Pendataan Ruas Jalan (Leger Jalan) pada Ruas Jalan Palembang - Betung - Sartika Nisumanti (UNIVERSITAS INDO GLOBAL MANDIRI, 2019)
AbstractAs national assets, roads are vital to establish the means of national development, especially in term of achieving balanced inter-regional development and equitable distribution of national outcomes. The Palembang-Betung road segment is managed in every fiscal year because it plays a key role in economic development for South Sumatra which links South Sumatra with other Provinces. This certainly leads to the change of the road condition, so it is necessary to collect data related to leger road for road network development plans and programs. Thus, this research issue is how to produce a Leger Road document which includes information about the Palembang - Betung road and its contents.This study aimed at identifying the overall asset data in the Palembang-Betung road section and then analyzing the data as an evaluation material for road maintenance in the form of leger road document data so that road segments need to be collected (road leger).The study results showed that Leger Road Documents had 5 parts, namely road summary cards, road cards (technical data), road cards (situations and pieces), album cards and bridge cards.The area of the Road owned space is 9,749,109 m2 of road segment. The average data of daily traffic for the km segment was 16 + 500 up to 17 + 250 equal to 33,034. The thickness of Road pavement was AC-WC = 0.04 m, AC –BC = 0.05, AC-Base = 0.075 m, Aggregate class A = 0.25 m, Aggregate class B = 0.30 m.The type of damage on road pavement was exfoliated with an area of 7.75 m², perforated area of 2.85 m², Crocodile cracking area of 7.62 m2, wavy area of 22.42 m², cracked lengthwise to an area of 7.86 m '.Keywords : Road Maintenance, Road LegerAbstrakJalan merupakan aset Negara yang pada hakekatnya mempunyai peranan penting dalam rangka mewujudkan sarana pembangunan Nasional, terutama yang menyangkut perwujudan perkembangan antar daerah yang seimbang dan pemerataan hasil pembangunan. Ruas jalan Palembang-Betung setiap tahun anggaran dilakukan penanganan karena ruas jalan ini memegang peranan penting sebagai roda perekonomian di Sumatera Selatan karena menghubungkan Provinsi Sumatera Selatan dengan Provinsi lainnya. Hal ini tentunya membawa perubahan kondisi pada ruas jalan ini, maka perlu dilakukan pendataan leger jalan untuk penyusunan rencana dan program pembinaan jaringan jalan.Permasalahan pada penelitian ini adalah Bagaimana cara menghasilkan Dokumen Leger Jalan yang memuat informasi mengenai ruas jalan Palembang – Betung beserta isinya. Penelitian ini untuk mengetahui data aset secara keseluruhan yang terkandung pada ruas jalan Palembang- Betung kemudian dilakukan analisa data sebagai bahan evaluasi untuk perawatan jalan yang berupa data dokumen leger jalan sehingga perlu dilakukan pendataan ruas jalan (leger jalan).Hasil penelitian Dokumen Leger Jalan di bagi menjadi 5 bagian yaitu kartu ringkasan jalan, kartu jalan (data teknik), kartu jalan (situasi dan potongan), kartu album dan kartu jembatan.Luas area Ruang Milik Jalan diperoleh 9.749.109 m2 persegmen ruas jalan. Data lalu lintas Harian rata-rata untuk segmen km. 16 + 500 s/d 17 + 250 sebesar 33.034. Perkerasan jalan diperoleh tebal AC-WC = 0,04 m, AC –BC= 0,05, AC-Base= 0,075 m, Agregat klas A = 0,25 m, Agregat klas B = 0,30 m.Jenis kerusakan yang terjadi pada perkerasan jalan adalah terkelupas dengan luas 7,75 m², berlubang luas 2,85 m², Retak Buaya luas 7,62 m2, bergelombang luas 22,42 m², Retak Memanjang luas 7,86 m’.Kata kunci : Pemeliharaan Jalan, Leger Jalan